Determination of Premenstrual Symptoms, Anthropometric Characteristics and Muscular Endurance of Store Employees with Premenstrual Syndrome - Tuzun, E. H.; Eker, L.; Kadioglu, E.; Ozalp, G.; Ovgun, Demiralp C. (Springer London Ltd, 2023)
[Abstract Not Available]